Tick-borne encephalitis virus infects human brain microvascular endothelial cells without compromising blood-brain barrier integrity - Palus, Martin; Vancova, Marie; Sirmarova, Jana; Elsterova, Jana; Perner, Jan; Ruzek, Daniel (Virology, 2017)
Alteration of the blood-brain barrier (BBB) is a hallmark of tick-borne encephalitis (TBE), a life-threating human viral neuroinfection. However, the mechanism of BBB breakdown during TBE, as well as TBE virus (TBEV) entry into the brain is unclear. Here, primary human microvascular endothelial cells (HBMECs) were infected with TBEV to study interactions with the BBB. Although the number of infected cells was relatively low in culture (<5%), the infection was persistent with high TBEV yields (>106pfu/ml). Infection did not induce any significant changes in the expression of key tight junction proteins or upregulate the expression of cell adhesion molecules, and did not alter the highly organized intercellular junctions between HBMECs. In an in vitro BBB model, the virus crossed the BBB via a transcellular pathway without compromising the integrity of the cell monolayer. The results indicate that HBMECs may support TBEV entry into the brain without altering BBB integrity.
Keywords: Tick-borne encephalitis virus; Virus Internalization; mozek; Neuroinfection; Blood-Brain Barrier; Encephalitis, Tick-Borne; viry klíšťové encefalitidy; internalizace viru; Blood-brain barrier; Encephalitis Viruses, Tick-Borne; Endothelial Cells; lidé; endoteliální buňky; Brain; Humans; klíšťová encefalitida; Tick-borne encephalitis; hematoencefalická bariéra